Types of Curculionidae (Coleoptera: Curculionoidea) housed at the Museo de La Plata entomological collection - Lanteri, Analía Alicia (2003)
This contribution about types of Curculionidae (Coleoptera: Curculionoidea) housed at the Museo de La Plata (MLP), updates the information on the material incorporated to the collection during the last ten years. The 111 types examined herein, correspond to 52 species assigned to the following subfamilies: Curculioninae (5 spp.), Cryptorhynchinae (8 spp.), Cyclominae (4 spp.), Entiminae (31 spp.), and Erirhininae (4 spp.). The authors of the species are C. Bordón, W. Clark, K. Heller, A. Lanteri, J. Morrone, C. O’Brien, P. Posadas, F. Ocampo, and G. Wibmer. The information provided is as follows: valid and original names of each species, bibliographic references, category of the types, code-numbers according to the rules of the MLP collection, sex of the specimens when it is determined, data on the labels (exact transcription), and additional information on the conservation of the type specimens.